(untitled) (Research, Society and Development, 2022)
In a context of dialogue between literature and medicine, the latter dealing with the human condition and its characteristics, we have the physician as an important assistant, prioritizing listening, proposing, and guiding the conduct directed to the patient. This is the main actor in the scenario of humanized care. Thus, this study compiles the information available in scientific productions about the impact of the approach of medical students to literary production during their training. Integrative literature review with a search carried out in the virtual libraries BVS, SciELO, and PubMed, with eight articles analyzed. These were divided into three axes: a) behavioral change, b) sensitivity and ethical issues, and c) critical thinking, communication, and dialogue. Teaching the art of medicine goes beyond technical-scientific training: it is necessary to increasingly prepare future physicians to deal with the dilemmas, conflicts, and plurality of opinions in the health field and medicine.